Frequency and Pattern of Congenital Heart Diseases in Newborn in a Tertiary Care Hospital - Uddin, Md Belal; Hossain, Md Belal; Rahman, Khalilur; Sultana, Nigar; Tarafder, Md Manirul Haque; Halim, Md Rustom (TAJ: Journal of Teachers Association, 2019)
Congenital heart disease is most common heart disease in children and causes significant morbidity and mortality. This study was done to evaluate the frequency and pattern of congenital heart disease in neonates (age ≤ 28 days) admitted in a tertiary care level hospital. It was a cross-sectional descriptive type of study conducted at the Department of Paediatrics of Rajshahi Medical College Hospital from January 2014 to December 2015. Among the 4120 neonates admitted in RMCH in that period, 52 cases had cardiac murmur on auscultation. Incidence of cardiac murmur in the newborn was 1.26%. Clinically, among the 52 cases, 40 cases were thought to have pathological murmur and 12 cases were thought to have innocent murmur. During echocardiography, structural cardiac defect (congenital heart disease) was detected in 38 cases. So, incidence of congenital heart disease was 9.22/ 1000 live births. Remaining 14 cases had normal cardiac anatomy in echocardiography. VSD (12 cases) was the most common type of acyanotic congenital heart disease (23.08%) followed by ASD (11 cases) and PDA (6 cases). Among the cyanotic congenital heart disease, tetralogy of Fallot was the most common abnormality and it was found in 4 cases (7.69%). In this study, parental consanguinity was detected in 4 cases (7.69%). Early diagnosis, timely referral and proper management of congenital heart can save valuable lives and allow normal growth and development. TAJ 2018; 31(2): 35-38